PENGEMBANGAN KARAKTER RELIGIUS PESERTA DIDIK MELALUI METODE PEMBIASAAN - Wahyu Hapsari, Halindri Intan; Suyitno; Widiastuti, Sripit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focuses on efforts to develop students’ religious character through habituation methods at UPT SD Negeri 2 Kepanjenlor, Blitar City. The research was conducted using a qualitative descriptive design with a case study approach. Data were collected from the school principal, teachers, students, and various supporting school documents. The data collection process involved in-depth interviews, direct observation, and documentation. Based on the findings, it can be concluded that the development of students’ religious character at the school is carried out through routine and structured habituation activities, such as daily prayers, recitation of Asmaul Husna, congregational dhuha and dzuhur prayers, tahfidz activities, and the Bank Central Akhirat (BCA) social program. In addition, the school also organizes religious activities including Ramadan boarding programs, Isra’ Mi’raj commemorations, religious study sessions, donations to orphans, and Qur’an completion ceremonies. All of these programs are integrated with school policies, such as Character Education Strengthening (PPK), the Pancasila Student Profile Strengthening Project (P5), and SERENADA (Religious, Nationalist, and Cultured School). The habituation method is considered effective in shaping students’ religious character because it is implemented consistently, systematically, and supported by teacher role models as well as parental involvement.